2010
DOI: 10.1111/j.1469-7610.2010.02323.x
|View full text |Cite
|
Sign up to set email alerts
|

Impaired attention to the eyes of attachment figures and the developmental origins of psychopathy

Abstract: The findings provide the first evidence that impairments in eye contact, previously shown during computer tasks, characterise psychopathic traits in young males.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
134
0
5

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(153 citation statements)
references
References 31 publications
12
134
0
5
Order By: Relevance
“…The LowCUHighODD and HighCU-HighODD groups were less accurate than the control group in processing the information in a go/no-go task, specifically when the stimuli expressed happiness, fear or neutral. These results indicate that a deficit in emotion processing is not restricted to specific emotions reflecting distress, such as fear or sadness, but points to a global impairment in emotion processing (distressing and not distressing) in children high in these constructs, as proposed by Dadds et al [23]. The LowCUEmotion in Oppositionality and CU 15 15 HighODD and HighCU-HighODD groups differed more markedly from the control group in the quality of the response (correct/wrong responses) rather than in the reaction time, for which most of the differences were in the HighODD without CU traits group, suggesting that the difficulties children with high CU traits and conduct problems have in processing emotions are more of an emotional rather than an attentional nature.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…The LowCUHighODD and HighCU-HighODD groups were less accurate than the control group in processing the information in a go/no-go task, specifically when the stimuli expressed happiness, fear or neutral. These results indicate that a deficit in emotion processing is not restricted to specific emotions reflecting distress, such as fear or sadness, but points to a global impairment in emotion processing (distressing and not distressing) in children high in these constructs, as proposed by Dadds et al [23]. The LowCUEmotion in Oppositionality and CU 15 15 HighODD and HighCU-HighODD groups differed more markedly from the control group in the quality of the response (correct/wrong responses) rather than in the reaction time, for which most of the differences were in the HighODD without CU traits group, suggesting that the difficulties children with high CU traits and conduct problems have in processing emotions are more of an emotional rather than an attentional nature.…”
Section: Discussionmentioning
confidence: 53%
“…Failure to identify fear and sadness in others facilitates a lack of inhibition of aggressive behaviours, as these expressions are not identified as aversive. On the other hand, Dadds et al [23] indicated that a general deficit in attention to relevant emotionally salient stimuli underlies callous-unemotional traits, which results in cascading errors in the development of moral conscience and empathy . Amygdala dysfunction in responding especially to fear but also to a variety of facial expressions has been suggested as the neurological basis of emotion recognition deficit [24,25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Los últi-mos, son los que parecen progresar hasta la adolescencia, como resultado de estilos de crianza caracterizados por su baja calidez (Kochanska, Kim, Boldt, & Yoon, 2013;Kroneman, Hipwell, Loeber, Koot, & Pardini, 2011;Waller, Gardner, & Hyde, 2013). Los problemas de conducta severos parecen asociarse con estilos de apego desorganizados (Pasalich, Dadds, Hawes, & Brennan, 2012), en los que parece haber menos contacto visual tanto con padres como con madres en situaciones de juego libre, esto en independencia del déficit de atención con hiperactividad, los problemas de conducta que presentan (Dadds, Jambrak, Pasalich, Hawes, & Brennan, 2010) y los bajos niveles de afecto físico y verbal con sus padres . Así, las madres de niños con problemas severos de conducta, que además tenían una relación deficiente con las figuras de autoridad o carencia de culpa, han reportado menor involucramiento materno y parentalidad positiva, que las madres con niños con problemas menores de conducta (Wall, Frick, Fanti, Kimonis, & Lordos, 2016).…”
Section: Introductionunclassified
“…Indeed, evidence suggests that anxiety in CU youth alters emotional processing, and points to variation in the processes underlying the cognitive, temperamental, and behavioral styles typical to CU traits. Among youth with high levels of CU, anxiety is associated with greater attention to others' distress cues (Kimonis, Frick, Cauffman, Goldweber, & Skeem, 2012) than CU-only counterparts, in contrast to the decreased attentiveness to these cues thought to contribute to AB in CU youth (Dadds et al, 2011). Only one existing study has examined attention to others' distress cues as a function of CU and anxiety , and while Kimonis and colleagues' findings provide preliminary information on patterns of emotional deficits among CU youth, further research incorporating observational paradigms is needed to examine how such anxiety-CU interaction patterns may influence corresponding behavioral heterogeneity.…”
Section: Impact Of Anxiety On Attention Biases In Cumentioning
confidence: 89%